Auto-mat dryer - Siti Maisarah, Aziz; Nurulhuda, Mohammad Yusoff (2020)
Home accidents cases in Malaysia are contributed by falls on the same level that due to slipping, tripping and stumbling. Home injury mainly happened because of not fully dried foot that led to slipping. The standard Foot mat used at home is not user friendly because it can lead to slippery. One of the main problems the inconvenient foot mat is always in net condition. Therefore, an invention named AUTO-MAT is introduced as an alternative way to upsize the drying capability compared to standard foot mat. The main components of AUTO-MAT Dryer include nichrome, polyvinyl chloride (PVC), rubber sheet, fans and 12V DC This foot dryer is designed by adding axial Fan, heating element powered by electric and activated by a mere of touch and pressure. This foot dryer is able to minimize the home injury caused by slipping and Falling. The-AUTO-MAT Dryer is an effective, simple, Low cost and has a potential to he patented and commercialized.